The - Hart, H. L. A. (Wiley-Blackwell, 1961)
The Concept of Law is the most important and original work of legal philosophy written this century. First published in 1961, it is considered the masterpiece of H.L.A. Hart's enormous contribution to the study of jurisprudence and legal philosophy. Its elegant language and balanced arguments have sparked wide debate and unprecedented growth in the quantity and quality of scholarship in this area--much of it devoted to attacking or defending Hart's theories. Principal among Hart's critics is renowned lawyer and political philosopher Ronald Dworkin who in the 1970s and 80s mounted a series of challenges to Hart's Concept of Law. It seemed that Hart let these challenges go unanswered until, after his death in 1992, his answer to Dworkin's criticism was discovered among his papers